2018
DOI: 10.1002/adma.201704501
|View full text |Cite
|
Sign up to set email alerts
|

Defective Metal‐Organic Frameworks

Abstract: The targeted incorporation of defects into crystalline matter allows for the manipulation of many properties and has led to relevant discoveries for optimized and even novel technological applications of materials. It is therefore exciting to see that defects are now recognized to be similarly useful in tailoring properties of metal-organic frameworks (MOFs). For instance, heterogeneous catalysis crucially depends on the number of active catalytic sites as well as on diffusion limitations. By the incorporation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
449
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 535 publications
(491 citation statements)
references
References 157 publications
7
449
2
5
Order By: Relevance
“…Metal–organic frameworks (MOFs), a kind of crystalline porous materials constructed by connecting metal ions/clusters and bridging organic ligands via coordination bonds, have been extensively studied for applications in catalysis, gas storage and separation, drug delivery, and sensing owing to their tailorable structure and function, ultrahigh porosity and large surface area. Although many promising methods have been applied to prepare multifunctional MOFs, such as modulating crystal structure and compounding with other functional materials, their performance still needs great improvement. Since the discovery of graphene, two‐dimensional (2D) materials, which possess the characteristics of large surface area and relatively high surface energy, have been found that the unique physicochemical properties cannot be achieved by their bulk counterparts …”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs), a kind of crystalline porous materials constructed by connecting metal ions/clusters and bridging organic ligands via coordination bonds, have been extensively studied for applications in catalysis, gas storage and separation, drug delivery, and sensing owing to their tailorable structure and function, ultrahigh porosity and large surface area. Although many promising methods have been applied to prepare multifunctional MOFs, such as modulating crystal structure and compounding with other functional materials, their performance still needs great improvement. Since the discovery of graphene, two‐dimensional (2D) materials, which possess the characteristics of large surface area and relatively high surface energy, have been found that the unique physicochemical properties cannot be achieved by their bulk counterparts …”
Section: Introductionmentioning
confidence: 99%
“…Even among hierarchical MOFs, those with interconnected extrinsic meso‐/macropores will have significant advantages in catalysis. There is also a need to further understand how defect sites could affect catalysis . As low‐dimensional MOFs have a greater external surface area; these surfaces are typically defective.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…These materials have unique structural features, such as permanent, regular porosity, and large internal surface areas . The enormous variety in MOF structures arises from the diversity of choice in metal structural building units (SBUs) and organic linkers, leading to an extensive spectrum of physical and chemical properties . This, along with the presence of various interactions, including hydrogen bonding, van der Waals interactions, π–π stacking, and metal coordination, have made MOFs promising functional compounds.…”
Section: Introductionmentioning
confidence: 99%